How children with juvenile idiopathic arthritis view participation and communication in healthcare encounters: a qualitative study - Veronica Lundberg; Catharina Eriksson; Torbjörn Lind; Imelda Coyne; Anncristine Fjellman-Wiklund (BMC, 2021)
Abstract Background Children report that they do not participate in their healthcare as much as they want, despite having the lawful right to form their own views and the right to express those views freely in all matters affecting them. Children and parents appeared to be more satisfied when healthcare professionals (HCP) use a participatory style in healthcare encounters. Aim To explore how children, adolescents and young adults with Juvenile Idiopathic Arthritis (JIA) and parents of children with JIA view their participation and communication in healthcare encounters with healthcare professionals. Methods Using a qualitative study design, participatory workshops were held separately for children and young adults with JIA and parents of children with JIA. The workshop data were analysed with Graneheim and Lundman's Qualitative Content Analysis resulting in one main theme and two subthemes. Results The theme "Feeling alienated or familiar with healthcare encounters" illuminates how children felt alienated at healthcare encounters if they found the encounters emotionally distressing. Children could withhold information regarding their health and function from both HCPs and their family and friends. The subtheme "Distancing oneself from healthcare" describe why children felt reluctant to engage in the healthcare encounters and experienced difficulty expressing how they really felt. The subtheme "Being a normal event in life" describe how children felt more comfortable over time engaging with HCPs when they knew what would happen, and felt that HCPs gave them the necessary support they needed to participate. Conclusions Children's participation in healthcare encounters varied depending if children felt alienated or familiar to the healthcare situations. Children distance themselves and are reluctant to engage in healthcare encounters if they find them emotionally distressing and feel disregarded. Over time, children can become more familiar and at ease with healthcare situations when they feel safe and experience personal and positive encounters. When the children are prepared for the encounter, provided with the space and support they want and receive tailored help they are more enabled to participate.